2021
DOI: 10.1111/jocd.14297
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 pandemic in dermatology outpatient clinics in Turkey: A survey study

Abstract: Background The COVID‐19 pandemic has substantially affected the healthcare systems around the world. It has also induced some changes in working habits at dermatology clinics. The majority of dermatology clinics limited the number of patients at outpatient clinics and postponed the elective procedures. Aims and Objectives To evaluate the working conditions and habits of dermatologists in Turkey during the COVID‐19 pandemic. Methods This is a survey study with seventeen questions in which two hundred fifteen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, the relocations of dermatologists created staff shortfalls in dermatology OPDs. 9,19 For a limited period, Thailand's COVID-19 prevention policies also placed severe restrictions on the conduct of cosmetic procedures throughout many areas of Thailand, including Bangkok, where our hospital is situated.…”
Section: Original Article Smjmentioning
confidence: 99%
“…However, the relocations of dermatologists created staff shortfalls in dermatology OPDs. 9,19 For a limited period, Thailand's COVID-19 prevention policies also placed severe restrictions on the conduct of cosmetic procedures throughout many areas of Thailand, including Bangkok, where our hospital is situated.…”
Section: Original Article Smjmentioning
confidence: 99%
“…To the editor, We would like to share ideas and experience on the publication "The Impact of COVID-19 Pandemic in Dermatology Outpatient Clinics in Turkey: A Survey Study. 1 " Ustaoglu concluded that "It is observed that the COVID-19 pandemic had affected the working habits and conditions of the dermatologists, which might be considered for the designing of new working approaches. 1…”
Section: Impact Of Covid-19 Pandemic In Dermatology Outpatient Clinicsmentioning
confidence: 99%
“…1 " Ustaoglu concluded that "It is observed that the COVID-19 pandemic had affected the working habits and conditions of the dermatologists, which might be considered for the designing of new working approaches. 1…”
Section: Impact Of Covid-19 Pandemic In Dermatology Outpatient Clinicsmentioning
confidence: 99%
“…The spectrum and prevalence of HSRDs vary depending on age, ethnicity and geographic region 9–19 . HSRD visits are influenced by the emergence of new diseases, novel therapies, changes in the healthcare system, public education campaigns and an aging population 20–28 . There is a scarcity of data on the prevalence of HSRD visits in the outpatient dermatological care setting.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] HSRD visits are influenced by the emergence of new diseases, novel therapies, changes in the healthcare system, public education campaigns and an aging population. [20][21][22][23][24][25][26][27][28] There is a scarcity of data on the prevalence of HSRD visits in the outpatient dermatological care setting. Studies assessing temporal trends in dermatological visits infrequently included HSRDs.…”
Section: Introductionmentioning
confidence: 99%